Quality by Design (QbD) Aided Formulation Optimization of Amlodipine Besylate Oral Thin Film - Kumar, Abhiram; Kumar, Madhaw; Singh, Romi; Upadhyay, Pratibha; Mukherjee, Anubhab (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Oral Thin Film (OTF) is an emerging approach for oral drug delivery but still there exists a scarcity of evidence for formulation optimization techniques. Herein, we aim to develop OTFs optimized by the QbD approach. Materials and Methods OTFs were prepared by solvent casting method using Amlodipine as an active ingredient and excipients such as Pectin, Aspartame, Tween 80, and Glycerine. The developed formulation was optimized using QbD software Design Expert version 8.0.4, USA. The independent variables of the experiment were selected as A-pectin, B-Tween-80, and C-glycerine, and the dependent variables were R1-tensile strength (kg/cm2), R2-permeation rate (μg/cm2/hr), R3-disintegration time (in a sec). Finally, the software suggested optimized formulation based on a desirability value closer to 1. Results The optimized oral films were comparatively evaluated and characterized by various techniques. The drug release was found to be ~96% at 10 min for OTFs and ~94% at 20 min for oral fast-dissolving tablets. The amlodipine was scanned in the UV range of 200 to 400 nm and the λmax was observed to be at 240±2 in a Phosphate of pH 6.8. Conclusion All results are found satisfactory and well within the acceptance range. This ensures that similar formulations can be optimized by using this technique in the future.
Keywords: Oral thin film (OTFs); Solvent casting method; Quality by design (QbD); Optimization; Drug release